Critical Remarks on Schmitt’s Political Realism - Sferrazza Papa, Ernesto C. (Religija ir kultūra, 2018)
According to a widely accepted line of interpretation, Carl Schmitt’s political philosophy is a classic example of political realism. In this article I propose, starting with an analysis of some themes from the essay published in 1923 Die geistesgeschichtliche Lage des heutigen Parlamentarismus, to challenge this interpretation. An in-depth analysis of Schmitt’s critique of parliamentarism and identitarian democracy may, in fact, suggest that his proposal is a normative theory of political enmity.